Pelatihan Peningkatan Berbicara Bahasa Inggris Dengan Metode Audio Lingual - Sidabutar, Usman (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The Audio Lingual (MAL) method refers to a very large learning competence in the ability to speak English. PPA Filadelpia Medan Foundation is an educational foundation that is oriented towards the progress of students to make children who are moral and achievers. This foundation also accommodates the children of the community who have a weak or underprivileged economy. Teachers who teach students have been set to become teachers who have a holistic spirit and dreams. Teachers who teach English and non-English subjects are very interested in learning English in order to develop their students. The trainer for Community Service Activities has a big heart to develop this foundation through English speaking training for teachers and foundation employees. The results conclude that the implementation of PKM activities starts from May 2021 to July 2021 for 12 times with meeting times with a total of 16 participants with system clusters. The Audio Lingual (MAL) method with a combination of Screen Cast O Matic becomes an instrument to carry out face-to-face training and online learning. The results of the observations prove that under the answers and learning outcomes through the audio lingual approach there is a tendency to learn, speak English and explore sources and information that are shown. This is evidenced by the statements of the respondents to prepare them in the world market which must be full of creativity that is flexible, directed, and achieved with high quality..